Development of two wheels space-frame plug-in hybrid electric motorcycle chassis - Muhammad Akmal, Jamaludin (2013)
This research deals with the development and analysis of the plug in hybrid electric motorcycle frame. The significance of this project is to offer additional space on the existing conventional motorcycle models. A 304 stainless steel hybrid electric motorcycle chassis was fabricated upon the completion of the Computer Aided Design (CAD) modelling as well as a Finite Element Analysis (FEA) specifically stress analysis of the modelled chassis. SolidWorks was used to conduct both the modelling and the stress analysis. The simulation results exhibited desirable minimum factor of safety which in turn ensures the structural integrity of the chassis. Round hollow 1.5 inch and 1 inch 304 stainless steel tubes were used to from the main part of the chassis. The tubes were rolled to conform specified design and joined by means of Tungstens Inert Gas (TIG) welding and Metal Inert Gas (MIG) welding.